Development of a blended learning-based electronic worksheet for students' writing skills - Rendy Nugraha Frasandy; Awida Awida; Aziqri Aulia; Exsaris Januar (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
The requirement for this final assignment to create a scientific paper requires reliable scientific writing skills. This study aims to develop blended learning-based electronic worksheet (EWs) on writing material for students of Elementary School Madrasah Teacher Education Study Program at Imam Bonjol State Islamic University Padang, Indonesia. The research method used is the development research from Thiagarajan with the 4D development model. The developed EWs is designed to improve students' writing skills through a combination of online and face-to-face learning. Data were collected through questionnaires and writing skills tests before and after the use of EWs. The results of the study indicate that the use of EWs assisted by blended learning can significantly improve students' writing skills. Student responses to EWs also showed positive results, with a high level of satisfaction with the materials and learning methods used. This study concludes that blended learning-based EWs is effective in improving the writing skills for students and contributing to the development of innovative learning methods in the digital era.